Not Written in Stone : Jews, Constitutions, and Constitutionalism in Canada - Michael Brown (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2003)
Using long-ignored constitutions of various Jewish organizations, this unique book uncovers the political history of Canadian Jewry since its beginning during the 1700s. Building on the premise that Jews, since time immemorial, have written down their values and ideologies, this study effectively demonstrates how these writings record the principles and values that motivated a community.